Avaliação da composição de Fungos Micorrizícos Arbusculares (Glomeromycota) em solos halomórficos no Rio Grande do Norte - Silva, Kássia Jéssica Galdino da (2021)
The coastal zone of Rio Grande do Norte State (RN) is the main focus of salt production in the country, significantly impacting the plant and microbial community, as well as the soil in this region. In this scenario, Arbuscular Mycorrhizal Fungi (AMF), as they form an obligatory symbiosis with plant roots, play an important role in this plant-soil system, increasing the tolerance of plant symbionts to stressful environments, such as saline ones. Thus, this thesis aimed to identify the diversity of the AMF community in a saline activity zone on the north coast of RN, seeking to understand the influence of salinity on this diversity. For this, four collections were carried out, during two consecutive periods of dry and rainy season, between NOV/2017 to JUN/2019 in three locations with different levels of salinity (saline in Macau [active saline], Reserva de Desenvolvimento Sustentável Estadual Ponta do Tubarão [negative control] and Galinhos [natural saline]) followed by physicochemical and taxonomic analyses. Thirty-seven species were identified, distributed in 19 AMF genera (Acaulospora, Ambispora, Dentiscutata, Cetraspora, Corymbiglomus, Claroideoglomus, Entrophospora, Fuscutata, Gigaspora, Glomus, Intraornatospora, Oehlia, Paradentiscutata, Paraglomus, Rhizoglomus, Racocetra, Sclerocystis, Scutellospora and Septoglomus), being the active saline environment the richest and most abundant in AMF species, when compared to the other two collection sites, with lower average salinity. Regarding the seasonal dry and rainy seasons, in general the dry season was richer in number of species and had greater abundance of spores. According to the UPGMA analysis, what most correlated the samples from the same area was the plant composition. However, the influence of salinity cannot be ruled out, since samples with higher salinity indices had lower species richness than samples with lower indices within the same collection area (Macau active salt). Therefore, more samples would be needed to statistically validate this observation. In addition to these results, a new species of the genus Acaulospora, which was the most abundant in the samples, was described, containing a double ornamentation with pit-shaped depressions, with spine-shaped projections inside, in a flat view the pits are connected as structures that look like channels. Along with the description of the new species, a review of the genus Acaulospora was carried out with phylogenetic analyzes using nrDNA sequences, which showed that Acaulospora is a monophyletic genus that also includes the species Kuklospora colombiana and K. kentinensis. Furthermore, we can conclude that the ornamentations described for the species of Acaulospora, despite being useful for the morphological description of species, constitute homoplastic characters due to the convergence of these characteristics in groups of species that do not share a more recent single ancestor. Spores of the species Corymbiglomus globiferum, also collected in the areas of this study, were used and deposited in the UFRN herbarium, analyzed and included in the article “Sieverdingia gen. nov., S. tortuosa comb. nov., and Diversispora peloponnesiaca sp. nov. in the Diversisporaceae (Glomeromycota)”.